Application of Smart Mobility in the DKI Jakarta Transportation System with KRL Commuter Line Transportation Mode - Damaris Bernike Bellastuti; Reza Fathurrahman (Pelopor Publikasi Akademika, 2023)
Congestion is one of the main problems of DKI Jakarta as the National Capital. Complex population mobility due to high population density and territory. Urban transportation problems can be solved by building strong, extensive, and effective transportation systems and networks to ensure a high level of accessibility. Electric Rail Train (KRL) Commuter Line is one of the alternative public transportation that is expected to anticipate and reduce congestion levels. The development of sustainable transportation pursued by the DKI Jakarta Provincial Government as one of the efforts to implement the Smart City concept, especially in the aspect of Smart Mobility. To get an overview of the implementation of the Smart Mobility project, there are three categories that support, namely accessibility, sustainability, and information technology systems. This research was conducted to find out how the development and contribution of KRL Commuter Line transportation modes in supporting the implementation of the Smart Mobility concept in DKI Jakarta. This research is a qualitative approach carried out using the comparative description method, which compares indicators of research variables with conditions that occur in the field. The results of this study state that all aspects of Smart Mobility have been achieved in the KRL Commuter Line transportation mode. In the aspect of accessibility, it can be seen from the number of stations, the number of train series, and the number of trips also increased from year to year. On the sustainable side, KRL Commuter Line can be considered environmentally friendly because it uses an emission-free and efficient source of electrical energy in the use of space, each KRL Commuter Line trip can accommodate up to 3,000 passengers. Aspects of information technology systems, which in terms of electronic payment systems PT KCI is open and adaptive to technological developments.